2017
DOI: 10.1002/hpm.2409
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐based financing in the heath sector in low‐ and middle‐income countries: Is there anything whereof it may be said, see, this is new?

Abstract: Whereas performance-based financing (PBF) is now developing fast in the health sector in low- and middle-income countries and is presented an innovative approach-concomitantly, subject to a separate research stream-it shares many features of the "managing for results" (MfR) and performance-based budgeting (PBB) currents that have existed for decades. In this paper, we first argue that PBF as currently developed in the health sector in low- and middle-income countries shares many features and thus can be viewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…A second causal mechanism identified in the process of this theory-driven evaluation is the fact that PBF appears to be acting on health workers’ motivation through a complex mechanism, all the more since beyond financial premiums, all contractual features and ancillary components of PBF are likely to impact on workers’ various sources of motivation. 21 Bertone and colleagues 22 have warned against the risk of looking at PBF payments in isolation, without reference to the overall remuneration of health workers. Their study confirms that the remuneration of health workers is complex and interrelated so that the different financial incentives cannot be examined independently.…”
Section: Resultsmentioning
confidence: 99%
“…A second causal mechanism identified in the process of this theory-driven evaluation is the fact that PBF appears to be acting on health workers’ motivation through a complex mechanism, all the more since beyond financial premiums, all contractual features and ancillary components of PBF are likely to impact on workers’ various sources of motivation. 21 Bertone and colleagues 22 have warned against the risk of looking at PBF payments in isolation, without reference to the overall remuneration of health workers. Their study confirms that the remuneration of health workers is complex and interrelated so that the different financial incentives cannot be examined independently.…”
Section: Resultsmentioning
confidence: 99%
“…We might therefore wonder whether the underlying theoretical rationale is not simply a pretext, which some might consider valid, to provide additional resources to the operational level of the health system, which in fact needs them. But is this incentive‐based logic worth the price, when other options to solve the health system's problems have not all been tested and PBF efficiency remains to be proven? The current state of knowledge is not yet adequate to answer this question in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…However, elements of PBF may foster both extrinsic and intrinsic motivation. Evidence on the motivational mechanisms of PBF remains scarce, but some studies have found that PBF can stimulate intrinsic forms of motivation, such as transforming the work environment [ 4 , 9 , 12 , 16 , 17 ], giving health workers opportunities to improve skills, enhancing recognition from the community [ 4 , 19 ], and strengthening professional pride and responsibility [ 9 , 19 ]. It thus appears that PBF as a complex systems intervention has the potential to influence many different types of motivational determinants [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%